The Effect of Liquidity, Leverage and Profitability on the Tax Aggressiveness of Manufacturing Companies - Lambok DR Tampubolon (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This research examines the impact of liquidity, leverage, and profitability on tax aggressiveness in manufacturing firms listed on the Indonesia Stock Exchange from 2017 to 2019. This analysis aims to collect empirical evidence on the effect of liquidity, leverage, and profitability on tax aggressiveness. The multiple linear regression process involves independent variables such as liquidity, debt, profitability, and the dependent variable tax aggressiveness. A purposive sampling procedure with unique parameters is used to assess the sample. According to this report's findings, liquidity and debt have little impact on tax aggressiveness, but profitability does